A Dublin core application profile for documenting analysis patterns in a reuse infrastructure. (1st January 2013) - Vegi, Lucas Francisco da Matta; Lisboa-Filho, Jugurta; Crompvoets, Joep; Soares, Liziane Santos; Braga, José Luís
Analysis patterns are reusable computational artefacts aimed at the analysis stage of the software development process. Although analysis patterns can facilitate the work of analysts and developers, the access to them is still very poor because of the way they are usually described and made available. In order to reduce these limitations as well as to support the cataloguing and to encourage the reuse of analysis patterns, the Analysis Patterns Reuse Infrastructure (APRI) was proposed. This infrastructure comprises a repository of analysis patterns documented through a specific metadata profile that can be accessed via web services. Based on the proposal of APRI, this paper introduces a machine-processable metadata profile suited to the documentation of analysis patterns, called Dublin Core Application Profile for Analysis Patterns (DC2AP). This metadata profile is described by RDF files identified via URI, thus providing linked data that increase the potential for reusing the analysis patterns.